PENDAMPINGAN DIGITAL MARKETING DAN PELATIHAN APLIKASI BUKU WARUNG DALAM MENINGKATKAN KINERJA KEUANGAN WARMINDO SUMULUR DAN MUDA MUDI - Nadila Cahyani; Ika Wulandari (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Culinary Micro, Small, and Medium Enterprises (MSMEs) such as Warmindo face major challenges in the form of limited digital marketing and manual and inefficient financial management, hampering business growth in the digital economy. This community service activity aims to increase the capacity of MSMEs through training and mentoring on Instagram-based digital marketing, as well as financial recording using a digital bookkeeping application. The methods used include training, hands-on practice, and ongoing mentoring. The activity partners are the managers of Warmindo Sumulur and Warmindo Muda Mudi. For financial management, the Bukuwarung application is used, which has a feature for systematically recording daily and monthly income and expenses. The results of the activity indicate an increase in MSMEs' understanding of cash book preparation and an increase in partners' interest and ability to implement digital financial bookkeeping. Prior to the activity, partners still relied on manual recording, which was ineffective and risky. After the training and mentoring, MSMEs were able to use the Bukuwarung application as a tool for digital and sustainable financial recording. The implications of this activity are increased financial management efficiency, cash flow transparency, and MSME readiness to adopt digital technology to support business decision-making and business sustainability in the digital economy era.